Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
f(x) = (0x - 3)(x + 4)
0x - 3 = 0 or x + 4 = 0
+ 3 + 3 - 4 - 4
0x = 3 x = -4
0 0
x = 0
f(x) = (0x - 3)(x + 4)
f(3) = (0(3) - 3)(3 + 4)
f(3) = (0 - 3)(7)
f(3) = (-3)(7)
f(3)= -21
(x, f(x)) = (3, -21)
or
f(x) = (0x - 3)(x + 4)
f(-4) = (0(-4) - 3)(-4 + 4)
f(-4) = (0 - 3)(0)
f(-4) = (0)(0)
f(-4) - 0
(x, f(x)) = (-4, 0)
0x - 3 = 0 or x + 4 = 0
+ 3 + 3 - 4 - 4
0x = 3 x = -4
0 0
x = 0
f(x) = (0x - 3)(x + 4)
f(3) = (0(3) - 3)(3 + 4)
f(3) = (0 - 3)(7)
f(3) = (-3)(7)
f(3)= -21
(x, f(x)) = (3, -21)
or
f(x) = (0x - 3)(x + 4)
f(-4) = (0(-4) - 3)(-4 + 4)
f(-4) = (0 - 3)(0)
f(-4) = (0)(0)
f(-4) - 0
(x, f(x)) = (-4, 0)
Assuming there really is 0
[tex]f(x)=(0x-3)(x+4)=-3(x+4)=-3x-12\\\\ -3x-12=0\\ -3x=12\\ \boxed{x=-4}[/tex]
[tex]f(x)=(0x-3)(x+4)=-3(x+4)=-3x-12\\\\ -3x-12=0\\ -3x=12\\ \boxed{x=-4}[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.